ACCURACY OF ENGLISH-INDONESIAN SCANLATION OF DETECTIVE CONAN MANGA AS COMPARED TO ITS JAPANESE-INDONESIAN TRANSLATION (ELT Forum: Journal of English Language Teaching, 2015)
Popularity of scanlated manga urged me to do this research. There are three main problems in this study: (1) to find out how the accuracy of English-Indonesia manga scanlation, (2) to find out differences between online manga (scanlated manga), and printed manga (Indonesian officially published manga) and (3) to find out which more accurate between both compared to original Japanese manga. At the end, I found that that although the scanlation of detective Conan manga is accurate but the printed manga was more accurate. Still, further research needed to analyze scanlation more detail. As readers of manga, we should be smarter by reading printed manga rather than online manga. This way we will get the better translation and also we can give our appreciation toward the author.